15.- GOTHIC ELEMENTS IN THREE WORKS OF EARLY SPANISH ROMANTICISM - Correoso Rodenas, José Manuel; Rigal Aragón, Margarita (Nueva Revista del Pacífico, 2021)
Abstract:The awakening of Gothic in literature in 1764 marked a milestone in the development ofthe Western literary canon. The inclusion of the supernatural and the horrific provoked theend of the reign of Enlightenment and opened the door for Romanticism. In Spain it took awhile longer for the new literary trend to flourish. However, a group of writers who hadpublished during the last decades of the eighteenth century started to include gothicelements in their works, creating Enlightenment-Gothic hybrids. Some of these authorswere Gaspar Melchor de Jovellanos, José Cadalso and Juan Meléndez Valdés. Their Eldelincuente honrado, Noches lúgubres, and “A Jovino, el melancólico,” respectively provethat gothic and sublime aesthetics also affected Spanish belles lettres.Resumen:El surgimiento de la literatura gótica en 1764 supuso un hito en el desarrollo del canonliterario occidental. La inclusión de lo sobrenatural y lo terrorífico provocó el final delreinado de la Ilustración y allanó el camino al Romanticismo. En España, su florecimientose haría esperar algo más. Sin embargo, un grupo de escritores que habían venidopublicando desde las últimas décadas del siglo XVIII comenzaron a incluir elementosgóticos en sus obras, creando híbridos entre el espíritu ilustrado y la literatura gótica.Algunos de esos autores fueron Gaspar Melchor de Jovellanos, José Cadalso y JuanMeléndez Valdés. Sus El delincuente honrado, Noches lúgubres y “A Jovino, elmelancólico”, respectivamente, prueban que las estéticas gótica y sublime ya se habíanintegrado en las belles lettres españolas.